Penelitian Fiksasi Rasa Dan Aroma Seledri - Endah Djubaedah; Enny H Lubis (Balai Besar Kimia dan Kemasan, 2001)
The research was aimed to study the quality changes of ;1avor fixative of celery leaves and celery seeds during storage and their acceptance by consumers. Two fixation formulas from two kinds of raw material were made i.e. (a) cellulose microcrystalline/sorbitol and (b) cellulose microcrystalline/sucrose. Shelf life of fixative products were tested at 0,30 and 60 days for their moisture contents, aroma stability, microbes and preference test on aroma and taste. The products of sorbitol from celery seed oleoresin and sucrose from celery seed were relatively better than these from celery leaves oleoresin because the moisture fixative of sorbitol and fixative of sucrosa 5,82 %, and 2,19 % respectively. The reduction of aromaof fixative of sorbitol was 3, 11 % and fixative of sucrose was 3, 79 % after 60 days of storage. The panel test from 12 panelists showed that products using sorhitol from the celery leaves 1